Engaging the corporate citizen: Social challenges, business solutions - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
When he came up with the idea of selling toilets in Cambodia, where more than 60 per cent of the population does not have access to basic sanitation, National Volunteer and Philanthropy Centre chief executive Laurence Lien was laughed at. His detractors told him: "Nobody is going to purchase toilets from you because this is a community that is dependent on (financial) aid. "But tens of thousands of the toilets were sold within the first few months. Speaking at the Africa Singapore Business Forum, Connex, held at Singapore Management University in August 2012, Lien credits the success of the project to its ability to engage small businesses to develop, manufacture and market the sanitation products.